Exploring perceived quality of life in long-term methadone-dependent patients: a qualitative study - Seyed Hamzeh Hosseini; Farnaz Fendereski; Fereshteh Yazdani; Zeinab Hamzehgardeshi (Harm Reduction Journal)
Abstract Background and aim Considering opioid use disorder (OUD) as one of the major global concerns, methadone maintenance treatment (MMT) has been documented the core treatment for such dependence in the affected individuals. With regard to the significant role of quality of life (QoL) in evaluating the outcomes of various treatment methods in this line, the present study was to explore perceived QoL in long-term methadone-dependent patients (MDPs). Materials and methods Applying a qualitative research design, this study was performed on 25 long-term MDPs, selected by purposive sampling with maximum variation. The data were also collected through semi-structured, in-depth interviews until data saturation was reached, and then analyzed via the MAXQDA10 software program and conventional content analysis. Results The themes mined from the qualitative data were (i) satisfaction with improvements of physical-mental deterioration, with two main categories, viz. (a) improved physical efficiency and (b) improved mental efficiency; (ii) satisfaction with having a meaning in life, comprised of two categories, i.e., (a) hope for the future and (b) new beginnings in life; (iii) positive self-perception, made up of four main categories of (a) Increased Confidence and Self-Acceptance, (b) Positive Self-Acceptance and Improved Self-Image, (c) Improved Decision-Making Abilities, and (d) More Effective Coping with Stressful Situations; (iv) satisfaction with perceived social capital, consisting of two categories, namely, (a) strong social support and (b) no worry of the stigma of substance use; (v) growth in marital satisfaction, with two main categories of (a) increased libido and (b) effective communication with one’s spouse; and (vi) physical-mental exhaustion caused by MMT, containing three categories, i.e., (a) fear of physical harm induced by MMT, (b) stigma and discrimination due to MMT, and (c) financial hardship following MMT. Conclusion The study results revealed that QoL in MDPs was associated with their satisfaction with improvements of physical-mental deterioration, satisfaction with having a meaning in life, positive self-perception, satisfaction with perceived social capital, growth in marital satisfaction, and physical-mental exhaustion caused by MMT. Accordingly, it was suggested to reduce the negative impacts of MMT, such as stigma and discrimination due to MMT and the related treatments, on QoL in opioid-dependent patients (ODPs) and boost its benefits in their daily life.